Light a lamp and look at the stock market - Radeef Chundakkadan (Financial Innovation, 2021)
In this study, we investigate the impact of the light-a-lamp event that occurred in India during the COVID-19 lockdown. This event happened across the country, and millions of people participated in it. We link this event to the stock market through investor sentiment and misattribution bias. We find a 9% hike in the market return on the post-event day. The effect is heterogeneous in terms of beta, downside risk, volatility, and financial distress. We also find an increase (decrease) in long-term bond yields (price), which together suggests that market participants demanded risky assets in the post-event day.
Keywords: 650; Behavioral finance; Covid-19; Event effect; Investor sentiment; Lockdown; Stock market